Development and Evaluation of Nanosuspension Incorporated in situ gel of Brimonidine Tartarate for Ocular Drug Delivery - Hanagandi, Viresh; Patil, Archana Sidagouda; Masareddy, Rajashree Shashidhar; Dandagi, Panchaxari Mallappa; Bolmal, Udaykumar Baburao (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: The goal of the study was to develop, optimize and in vitro-ex vivo investigation of Brimonidine tartrate nanosuspension incorporated in situ gel formulation to differentiate with marketed (formulation) eye drops for the efficient treatment of glaucoma. Materials and Methods: Nanosuspensions were formulated by solvent evaporation method using probe sonication technique. The effect of the independent variables Tween 80 and Pluronic F68 concentration on Nanosuspension properties were investigated by performing 32 factorial design of experiment. Nanosuspensions were characterized by measuring particle diameter and zeta potential, surface morphology, drug entrapment efficiency and then nanosuspensions were incorporated in to in situ gel base for in vitro release and ex-vivo corneal permeability studies and were differentiated with marketed product. Results and Discussion: The most excellent nanosuspension formulation system selected via the Design Expert 12 software program was F7 which contains 0.5% of Tween 80 and 3 % of Pluronic F68. An optimized nanosuspension formulation F7 showed an average particle diameter of 157.4±0.95 nm with PDI of 0.379 and a zeta potential of -19.1 mV. It had an average entrapment efficiency of 85.95±1.40%. It also showed 98.36±0.58% of drug being released in vitro when incorporated in to in situ gel base over 24 hr. F7 showed significantly greater drug permeation in comparison to the marketed eye drop formulation in ex vivo transcorneal permeability studies and was able of retaining its stability for 90 days. Conclusion: The developed nanosuspension incorporated in situ gel base formulation could be utilized as potential delivery system for long time management of glaucoma with once daily dose.
Keywords: Brimonidine Tartrate; Ocular bioavailability; Nanosuspension; In-situ gel; Increased residence time